Government Corruption: An Exogenous Factor in Companies' Victimization?. (4th March 2019) - Arellano-Gault, David
Abstract : When a country suffers from systemic corruption, several practices and routines are created in public and private organizations to normalize the processes that stabilize and reproduce the conditions for repetitive corrupt behavior. Through a survey on private companies in a major Mexican city and a set of interviews with two companies, this article shows how these organizations create the internal conditions for meeting the demand for a bribe on the part of public officials. This study uses empirical evidence to support that companies develop an endogenous response to corrupt practices due to the advantages of maintaining the agreement originally reached with corrupt public officials stable. Corruption then can be understood not just as a victimization of companies by governmental officials but also as a more intricate social and organizational process in which various actors engage in and justify their acts by constructing organizational responses in order to normalize them. These empirical findings (an issue on which it is usually extremely difficult to obtain evidence in the field) support the current literature critical on anticorruption measures that merely focuses on the public sector without understanding the social process that creates corruption, in this case, between companies and the public sector.